BACK TO HETERONOMY? THE MORALS OF CIVIC-MILITARY SCHOOLS - Daud, Rafael Pétta [UNESP]; Lastória, Luiz Antônio Calmon Nabuco [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2023)
To justify the implementation of Civic-Military Schools (ECIM) in the public education system, the federal government in office until 2022 positioned itself in favor of educational principles considered heteronomous. At the same time, he promised to adapt the measure to Brazilian educational legislation. This, usually points to the search for moral autonomy through the democratization of school. Faced with these notorious contradictions, this article aims to clarify what is, in fact, the purpose of moral education proposed by the main regulatory norm of pedagogical actions in an ECIM: the Guidelines for Civic-Military Schools (BRASIL, 2021). To this end, supported by the hermeneutic method, we analyzed the document, privileging its indications more directly related to the dimension of school coexistence. We conclude that the federal government in question, while establishing moral heteronomy as an educational principle for ECIM, took moral autonomy as a inferior principle, even suggesting it as a countervalue.
DE VOLTA À HETERONOMIA? A MORAL NAS ESCOLAS CÍVICO-MILITARES
Keywords: Civic-Military Schools; Democracy; Education; Moral Heteronomy